Enforcement of International Criminal Law Regarding Crimes in Armed Conflict - Febri Arwan Syah; Arifin Faqih Gunawan; Husni Thamrin (Jurnal Hukum dan Keadilan, 2026)
Armed conflicts, whether occurring between states or within the territory of a single state, frequently result in severe violations of human rights. Acts such as the deliberate killing of civilians, the deployment of prohibited weapons, enforced disappearances, and systematic torture represent only a fraction of the atrocities committed during wartime. In many instances, these crimes remain inadequately investigated and prosecuted, allowing perpetrators to evade legal accountability. The enforcement of international criminal law in situations of armed conflict faces numerous structural and institutional challenges. These include the limited jurisdictional reach of the International Criminal Court (ICC), political obstacles arising from the interests of members of the United Nations Security Council, and difficulties in collecting reliable evidence within active conflict zones. Such constraints often undermine efforts to ensure justice for victims and to hold offenders accountable under international law. This article provides a comprehensive examination of the normative framework and institutional mechanisms established within international criminal law to address war crimes, crimes against humanity, and genocide. Employing a normative-juridical and comparative research approach, the study evaluates the effectiveness of criminal prosecutions before the ICC, ad hoc international tribunals, and alternative accountability mechanisms, including Truth and Reconciliation Commissions. The findings reveal a persistent gap between the legal standards embodied in international instruments and their practical implementation in conflict-affected regions. This discrepancy is largely influenced by geopolitical interests that frequently interfere with legal processes and weaken the impartial application of justice. To address these shortcomings, the study proposes strengthening the institutional capacity of the ICC, reforming the Security Council referral mechanism, and enhancing cooperation between litigation-based and non-litigation accountability processes. Such integrated measures are essential for combating impunity and promoting justice in the context of contemporary armed conflicts.